1974
DOI: 10.1111/j.1365-2494.1974.tb01257.x
|View full text |Cite
|
Sign up to set email alerts
|

The Improvement of Hill Pastures for Agriculture

Abstract: In concluding the 1968 Symposium on hill land productivity (56), which has been taken as the starting point for this survey, the late Dr William Davies requested that someone prepare a blueprint for the overall development of hill lands and, more specifically, a scheme for agriculture which should include the full integration ot known facts into whole viable systems of husbandry. Since then, Walsh and Lee (111) have proposed a systems strategy for marginal land based on the concept of integrating oflF-farm fee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

1977
1977
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…The high proportion of fixed N in clover noted in this study has been observed by a number of workers in forage (Loginov, 1966;Trefachev and Khabarova, 1966;Simpson, 1965) and grain (Mouchova and Apltauer, 1968;Trefachev et al, 1967) legumes and is an indication of the importance of effective symbiosis in the hill pasture system (Walker et al, 1954;Newbould, 1974;Jones et al, 1964;Masterson, 1973).…”
Section: Discussionmentioning
confidence: 66%
“…The high proportion of fixed N in clover noted in this study has been observed by a number of workers in forage (Loginov, 1966;Trefachev and Khabarova, 1966;Simpson, 1965) and grain (Mouchova and Apltauer, 1968;Trefachev et al, 1967) legumes and is an indication of the importance of effective symbiosis in the hill pasture system (Walker et al, 1954;Newbould, 1974;Jones et al, 1964;Masterson, 1973).…”
Section: Discussionmentioning
confidence: 66%
“…Upland grasslands in Britain frequently have a low phosphate status (Newbould 1974) and the plant species present in upland grassland are often infected by VA mycorrhizal fungi (Ali 1969;Gerdemann & Nicolson 1963;Mejstrik 1972). Tropical grasses and legumes often respond to VA infections (Crush 1974;Mosse, Hayman & Arnold 1973;Mosse, Powell & Hayman 1976), but responses of temperate grasses to infection in Britain and New Zealand have been smaller and have developed more slowly (Ali 1976;Crush 1973a, b;.…”
Section: Introductionmentioning
confidence: 97%
“…An important aspect of the interaction between grass and clover, and therefore their compatibility, is the slower growth of clover at low temperatures (Williams, 1970;Newbould, 1974;Rhodes, 1981;Frame and Newbould, 1984). It seems likely, therefore, that clover is placed at a competitive disadvantage in the mixture, which may lead to suppression of clover yield in spring.…”
Section: Introductionmentioning
confidence: 99%